1997
DOI: 10.1097/00005768-199704000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Gymnastic training and bone density in pre-adolescent females

Abstract: Bone mineral density (BMD) was compared between 7-11-yr-old female gymnasts (GYM: N = 16) with a history of high volume impact loading (minimum of 15 h.wk-1 for past 2 yr) and healthy nonathletic controls (CON: N = 16). Whole body (WB) and regional areal BMD measures were determined by dual energy x-ray absorptiometry (DXA) normalized for height and body mass and also converted to bone mineral apparent density (BMAD). Volumetric BMD and bone cross-sectional areas were also measured by peripheral QCT (pQCT) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
69
5
10

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 32 publications
12
69
5
10
Order By: Relevance
“…These findings are in contrast to other reports of restrictive eating patterns in young elite (8,9) and college-age (1,7) gymnasts but similar to nonelite, but competitive, young gymnasts. (30,31) When normalized for FFST mass, protein intake was lower in gymnasts versus controls. Presently, the AI for calcium in 9-13 year olds is 1300 mg/ day.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings are in contrast to other reports of restrictive eating patterns in young elite (8,9) and college-age (1,7) gymnasts but similar to nonelite, but competitive, young gymnasts. (30,31) When normalized for FFST mass, protein intake was lower in gymnasts versus controls. Presently, the AI for calcium in 9-13 year olds is 1300 mg/ day.…”
Section: Discussionmentioning
confidence: 96%
“…These findings support the idea that artistic gymnastics training contributes to the development of high TB and site-specific BMD observed in child gymnasts. (18,(30)(31)(32) Several investigators report that FN and LS BMD begins to increase significantly at age 12, (33)(34)(35) with the greatest gains observed after the onset of puberty. (35) In females, the average annual rate of gain in FN and LS BMD is ∼4.9% and ∼4.8%, respectively, until age 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, estimated energy balance, BMI and serum levels of T 3 and IGF-I correlated positively with serum levels of bone formation markers in the amenorrheic distance runners (Zanker & Swaine 1998). Furthermore, leptin receptors have been found in bone (Bradley et al 1997, Dyson et al 1997, thus depression of leptin levels and suppression of the diurnal leptin rhythm associated with low energy intake may mediate not only reproductive function but also bone accretion. The osteopenia observed in amenorrheic athletes involved in sports emphasizing leanness may therefore be another adaptive response to chronic low energy intake.…”
Section: Skeletal Problemsmentioning
confidence: 95%
“…Few investigators have attempted to evaluate bone geometry in response to exercise; as a result, limited evidence has been provided for an effect of mechanical loading on bone architecture (1)(2)(3)(4)(5)(6)(7). Even fewer studies have demonstrated geometric adaptation to mechanical loading during growth (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%